Gendered mobility strategies and challenges to sustainable travel—patriarchal norms controlling women's everyday transportation - Lindkvist, Christina (Frontiers in Sustainable Cities, 2024)
Sweden is a country with an international reputation of gender equality. The political goal of gender equality is based on feminist analysis on what constitutes a just society according to gender and the fight against patriarchal norms. Despite policy recommendations and legislations that counteract discrimination against women, women still fear travelling by public transport and to be out in the evenings. This indicates that the Swedish society still has patriarchal norms to deal with. The aim with this article is to investigate gendered mobility strategies from a feminist perspective. The contribution is based on qualitative data and figures from national surveys (the travel survey and the time use survey). The former has been collected by interviews with women living in peripheral urban neighbourhoods in the three metropolitan regions of Sweden. The interviews explored mobility practices and strategies, experiences with different modes of transport, and reliability, affordability, and comfort of the mobility options available. Among other results, the analysis shows that travel choice for women is affected by their concerns about safety and by the related adaptation to situations identified as threatening. Moreover, women are still the main carer and conduct major parts of chauffeuring dependent family members. Managing everyday out-of-home activities is still a concern for many women, for their own safety and with consideration taken to dependent family members.